Flower-Like Mn-Doped CeO2 Microstructures: Synthesis, Characterizations, and Catalytic Properties - Ling Liu; Jingjing Shi; Xiaojun Zhang; Jianzhou Liu (Journal of Chemistry)
Mn-doped CeO2 flower-like microstructures have been synthesized by a facile method, involving the precipitation of metallic alkoxide precursor in a polyol process from the reaction of CeCl3·7H2O with ethylene glycol in the presence of urea followed by calcination. By introducing manganese ions, the composition can be freely manipulated. To investigate whether there was a hybrid synergic effect in CH4 combustion reaction, further detailed characteristics of Mn-doped CeO2 with various manganese contents were revealed by XRD, Raman, FT-IR, SEM, EDS, XPS, OSC, H2-TPR, and N2 adsorption-desorption measurements. The doping manganese is demonstrated to increase the storage of oxygen vacancy for CH4 and enhance the redox capability, which can efficiently convert CH4 to CO2 and H2O under oxygen-rich condition. The excellent catalytic performance of MCO-3 sample, which was obtained with the starting Mn/Ce ratios of 0.2 in the initial reactant compositions, is associated with the larger surface area and richer surface active oxygen species.